2018
DOI: 10.1002/cpp.2335
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical utility of the concept of self‐disgust

Abstract: This systematic literature review examined the clinical utility of the construct of self‐disgust in understanding mental distress. Specifically, the review assessed whether there is a shared conceptual definition of self‐disgust, the face and construct validity of the quantitative assessment measures of self‐disgust, and the predictive validity of self‐disgust in formulating the development of a range of psychological difficulties. A systematic database search supplemented by manual searches of references and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 87 publications
(170 reference statements)
3
26
0
Order By: Relevance
“…In Study 1 we demonstrated that self-disgust was positively associated with loneliness, anxiety and depression symptoms in older adults. These findings further extend previous research that showed a positive association between self-disgust and loneliness in older adults (Laffan et al, 2017;Ypsilanti, 2019), and a positive association between selfdisgust and anxiety symptoms in the general population (for a review see Clarke et al, 2019).…”
Section: Study 1 Discussionsupporting
confidence: 88%
“…In Study 1 we demonstrated that self-disgust was positively associated with loneliness, anxiety and depression symptoms in older adults. These findings further extend previous research that showed a positive association between self-disgust and loneliness in older adults (Laffan et al, 2017;Ypsilanti, 2019), and a positive association between selfdisgust and anxiety symptoms in the general population (for a review see Clarke et al, 2019).…”
Section: Study 1 Discussionsupporting
confidence: 88%
“…In relation to psychosis, self‐disgust can be understood as a maladaptive cognitive structure (Powell et al , ), one of the three categories of potential mediators between childhood trauma and psychosis recently outlined (Williams et al , ). Given the potential of self‐disgust to complicate and intensify other psychological difficulties (see Clarke et al , ), it is important for clinicians to explore experiences indicative of self‐disgust with clients with psychosis presenting with an abusive/traumatic history. Understanding and responding to such experiences is an important component of an effective formulation and therapy plan.…”
Section: Discussionmentioning
confidence: 99%
“…One variable which has not yet been researched in relation to psychosis but which is gaining significant interest as a transdiagnostic construct relevant to a number of mental health difficulties is self‐disgust (see Clarke et al , , for a review). Disgust, categorized as a primary emotion since the emergence of Darwinian concepts regarding the evolutionary function of human emotions (Rozin & Fallon, ), is commonly understood as an affective rejection response, with the overall purpose being the prevention of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Because the QASD has been shown to be a reliable tool for measuring the self‐disgust in mental disorders (Clarke, Simpson, & Varese, 2019; Ille et al, 2014; A. Schienle et al, 2014; A. Schienle, Leutgeb, & Wabnegger, 2015; A. Schienle, 2018), we believe that the QASD must be adapted for application to Chinese patients in future research. Thus, in order to advance the clinical research of self‐disgust in China, especially the relationship between self‐disgust and other psychopathology, we performed this study to translate the questionnaire for the assessment of self‐disgust (QASD) into Chinese and evaluate its validity and reliability among Chinese mental disorders.…”
Section: Introductionmentioning
confidence: 99%